"The good news about bad news": Feedback about past organisational failure and its impact on worker productivity - Sabrina Jeworrek; Vanessa Mertins; Michael Vlassopoulos (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2018)
Failure in organisations is a very common phenomenon. Little is known about whether past failure affects workers' subsequent performance. We conduct a field experiment in which we follow up a failed mail campaign to attract new volunteers with a phone campaign pursuing the same goal. We recruit temporary workers to carry out the phone campaign and randomly assign them to either receive or not receive information about the previous failure and measure their performance. We find that informed workers perform better - in terms of both numbers dialed (about 14% improvement) and completed interviews (about 20% improvement) - regardless of whether they had previously worked on the failed mail campaign. Evidence from a second experiment with student volunteers asked to support a campaign to reduce food waste suggests that the mechanism behind our finding relates to contextual inference: Informing workers/volunteers that they are pursuing a goal that is hard to attain seems to add meaning to the work involved, leading them to exert more effort.
urn:nbn:de:gbv:3:2-83667
Keywords: C93; J22; M50; 330; contextual inference; feedback; failure; field experiment; meaning of work